(untitled) (JOURNAL OF ADVANCES IN CHEMISTRY, 2015)
Mn3O4 nanoparticles have been successfully synthesized by a simple hydrothermal method at low temperatures. The processing conditions such as reaction temperature and time were optimized to synthesized phase pure nanocrystalline Mn3O4 with good electrochemical properties. The particles synthesized at a reaction temperature of 150Â°C for 12 h exhibited different characteristic peaks along with (211) predominant orientation which corresponds to tetragonal structure of Mn3O4 with space group I41/amd (141) and estimated crystallite size of 32 nm. The SEM analysis reveals that the octahedral shape of grains with an average grain size of 180 nm. The vibrational studies from Raman and FTIR measurements confirmed the microstructure and presence of Mn-O bonding. The conductivity of the product was increased with increasing temperature following the Arrhenius behavior with estimated activation energy of 0.37 eV. The supercapacitive performance of nanocrystalline Mn3O4 octahedrons in 1M Na2SO4 aqueous electrolyte exhibited a high specific capacitance of 348 Fg-1 at current density of 0.5 mAcm-2 and 70% capacitive retention even after 4000 cycles.